Conference Record of Papers Presented at the First Vehicle Navigation and Information Systems Conference (VNIS '89)
DOI: 10.1109/vnis.1989.98778
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of in-vehicle information systems in a real life freeway corridor under recurring and incident-induced congestion

Abstract: Prepared in cooperation with the State of California, Business and Transportation Agency, Department of Transportation. The contents of this report reflect the views of the authors who are responsible for the facts and accuracy of the data presented herein. The contents do not necessarily reflect the official views or policies of the State of California. This report does not constitute a standard, specification, or regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The modelling of the occurrence of such incidents, and the way in which the effects are propagated through the network is a major task; it is, however, an extremely important area to consider, since the full benefit of a DRG system may only be realised in such situations. We note that incident modelling has already received some attention in the context of route guidance systems (Al-Deek et al, 1989;Bi-eheret et al, 1990;Mauro, 1991).…”
Section: Variabilitvmentioning
confidence: 89%
“…The modelling of the occurrence of such incidents, and the way in which the effects are propagated through the network is a major task; it is, however, an extremely important area to consider, since the full benefit of a DRG system may only be realised in such situations. We note that incident modelling has already received some attention in the context of route guidance systems (Al-Deek et al, 1989;Bi-eheret et al, 1990;Mauro, 1991).…”
Section: Variabilitvmentioning
confidence: 89%
“…However, without such standards equipment on different vehicles and on different highways will be incompatible, much more expensive and far less productive. 20 …”
Section: Reference Models and Open Architecturementioning
confidence: 99%
“…Since we have no reliable understanding about how drivers plan on the basis of such information the planning layer reference model is likely to be more complex. It is to be hoped that experiments now underway [17,18,19,20] will improve our understanding.…”
Section: Ivhs Architecture For Partial Automationmentioning
confidence: 99%
“…For instance, in their Los Angeles study, they found that 93 incidents occurred per one million vehicle miles of travel, though just 6.5% of these incidents were collisions and just 10% of incidents blocked lanes (average duration of 20 minutes). Al-Deek et al (1988 modeled the occurrence of incidents in a highway corridor, and estimated benefits associated with diverting traffic to alternate routes. The dynamics of traffic flows during incidents was also studied by Heydecker (1994) within the context of alternative diversion strategies.…”
Section: Introductionmentioning
confidence: 99%